A building integrated photovoltaic (BIPV) demonstration building in Belgium with new fibre reinforced solar technology PV modules: analysis with simulation and monitoring data - Agathokleous, Rafaela; Kalogirou, Soteris A.; Pierret, Stéphane (My University, 2017)
New more flexible and lightweight photovoltaic (PV) modules based on a novel encapsulation technology with glass fibre reinforced composite materials are installed in a residential building in Mons, Belgium which is used as a demonstration building. The tested modules are named roofing shingles (RS) and they are installed on the south part of the building’s roof with inclination angle 40⁰. The installation comprises of 54 RS modules of 32 monocrystalline Silicon cells each. The total installed power of the system is 7.01 kWp. The BIPV system installed on the Belgian demo site is monitored to observe its performance and optimise the installation in case of efficiency loss due to natural parameters e.g. overheating. Various equipment like temperature, humidity, radiation sensors, data loggers etc., are installed on the building for the monitoring. Prior to the installation, a simulation model in TRNSYS simulation software is carried out using weather data for Belgium from a Typical Meteorological Year (TMY) file, to predict the performance of the system as well as other various parameters such as the developed temperature on the PVs surface, air gap temperature etc. The aim of this study is to present the performance of the BIPV system on the demo site and compare the monitoring data with the simulation results. It is concluded that the results from the simulation agree with the monitoring results measured on site.
Keywords: Building integrated PV; Fibre Reinforced Solar Technology PV; Simulation; Monitoring